Rpadrino: An R package to access and use PADRINO, an open access database of Integral Projection Models. Issue 9 (23rd June 2022) - Levin, Sam C.; Evers, Sanne; Potter, Tomos; Guerrero, Mayra Peña; Childs, Dylan Z.; Compagnoni, Aldo; Knight, Tiffany M.; Salguero‐Gómez, Roberto
Abstract: Discrete time structured population projection models are an important tool for studying population dynamics. Within this field, integral projection models (IPMs) have become a popular method for studying populations structured by continuously distributed traits (e.g. height, weight). Databases of discrete time, discrete state structured population models, for example DATLife (life tables) and COMPADRE & COMADRE (matrix population models), have made quantitative syntheses straightforward to implement. These efforts allow researchers to address questions in both basic and applied ecology and evolutionary biology. Since their introduction in 2000, over 300 works containing IPMs have been published, offering opportunities for ecological synthesis too. We describe a novel framework to quickly reconstruct these models for subsequent analyses using Rpadrino R package, which serves as an interface to PADRINO, a new database of IPMs. We introduce an R package, Rpadrino, which enables users to download, subset, reconstruct, and extend published IPMs. Rpadrino makes use of recently created software, ipmr, to provide an engine to reconstruct a wide array of IPMs from their symbolic representations and conduct subsequent analyses. Rpadrino and ipmr are extensively documented to help users learn their usage. Rpadrino currently enables users to reconstruct 280 IPMs from 40 publications that describe the demography of 14 animal and 26 plant species. All of these IPMs are tested to ensure they reproduce published estimates. Rpadrino provides an interface to augment PADRINO with external data and modify parameter values, creating a platform to extend models beyond their original purpose while retaining full reproducibility. PADRINO and Rpadrino provide a toolbox for asking new questions and conducting syntheses with peer‐reviewed published IPMs. Rpadrino provides a user‐friendly interface so researchers do not need to worry about the database structure or syntax, and can focus on their research questions and analyses. Additionally, Rpadrino is thoroughly documented and provides numerous examples of how to perform analyses which are not included in the package's functionality. Resumen: Los modelos de proyección de población estructurados de tiempo discreto son una herramienta importante para estudiar la dinámicas poblacionales. Dentro de este campo, los Modelos de Proyección Integral (IPM, en inglés) se han convertido en un método popular para estudiar poblaciones estructuradas de acuerdo con rasgos continuos (por ejemplo, altura, peso). Existentes bases de datos demográficas de tiempo discreto, como por ejemplo DATLife (tablas de vida) y COMPADRE & COMADRE (modelos matriciales de población), han facilitado síntesis cuantitativas. Dichos esfuerzos han permitido a los investigadores abordar cuestiones tanto en ecología básica como aplicada y biología evolutiva. Desde su introducción en el año 2000, se han publicado más de 300 trabajos basados en IPMs, los cuales también ofrecen oportunidades para la síntesis ecológica. Aquí describimos un marco novedoso para reconstruir rápidamente estos modelos para posteriores análisis utilizando el paquete de R Rpadrino, el cual sirve como interfaz para PADRINO, una nueva base de datos de IPMs. Presentamos el paquete de R Rpadrino, el cual permite descargar, crear subconjuntos, reconstruir y extender IPM publicados. Rpadrino hace uso del software creado recientemente, ipmr, para proporcionar el motor necesario para reconstruir una amplia gama de IPMs a partir de sus representaciones simbólicas y a partir de los cuales realizar análisis. Rpadrino e ipmr están ampliamente documentados para ayudar a sus usuarios a conocer su uso. Actualmente, Rpadrino permite reconstruir 280 IPM de 40 publicaciones, las cuales describen la demografía de 14 especies de animales y 26 de plantas. Estos IPM han sido cuidadosamente investigadoes para garantizar que reproduzcan las estimaciones publicadas. Rpadrino proporciona una interfaz para aumentar PADRINO con datos externos y modificar los valores de los parámetros, creando una plataforma para ampliar los modelos más allá de su propósito original y manteniendo la total reproducibilidad. PADRINO y Rpadrino conforman una caja de herramientas para examinar nuevas preguntas y realizar síntesis con IPMs publicados. Rpadrino proporciona una interfaz fácil de usar para que los investigadores no tengan que preocuparse por la estructura o la sintaxis de la base de datos y puedan concentrarse en sus preguntas y análisis. Además, Rpadrino está completamente documentado y proporciona numerosos ejemplos de cómo realizar análisis que no están incluidos en la funcionalidad del paquete.